Educational Activities in the Period of Hitler’s National Socialist Youth - Milenović, Živorad M; Rajcevic, Petar (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
This paper reviews the educational activity during Hitler's National Socialist Youth and its two branches: Hitlerjugend and The League of German Girls. Both of these branches were established during the Weimar Republic, but acquired extreme features after 1933. The Nazis realized early on the importance of educating German youth to achieve the party's strategic goals—creating the pure Aryan race, Germany as the world's leading power in political, military, economic and cultural terms, and the German people to rule the world as the most civilized people with their superior tradition and culture. Educational activities from this period were focused on eugenics, totalitarian, militaristic, racist, ideological, anti-Semitic, occult and other inhuman, anti-human and anti-pedagogical principles. In addition to the numerous negative consequences, it left in the history of pedagogy; it contributed to the destruction of an entire generation of German children and youth. For this reason, there is the need for a more detailed study of this topic in order to warn of the consequences that would occur in the future if education was ever again based on the principles of Hitler's National Socialist Youth in Nazi Germany.
Keywords: education; Nazi Germany; Nazism; Hitlerjugend; The League of German Girls; eugenics; ideology; racism; anti-Semitism; occultism